Postmodern Perspective towards Human Health and Illness - Karki, Binod Kumar (KMC Research Journal, 2020)
Health and illness, as widely used terms in postmodern society leave a wide scope as to their definition and conceptual interpretation. The medico-technical perspective refers to health and illness as objective changes in the structure and functioning of the human body and mind, as a result of which the bodily and mental integrity of the human organism is affected detrimentally. On the contrary, the social sciences, and especially medical sociology, define health and illness essentially in terms of the social system within which they occur. The main task of medical sociology is to pay attention to those social systemic and sociocultural aspects of health and illness which are sometimes grossly neglected or insufficiently understood by the medical sciences, thereby to contribute to a comprehensive approach to these phenomena.This study is based on review of the related literature to postmodern perspective towards health and illness. The aim of this study is to explore the postmodernist perspective towards health and illness. Thus, I will be exploring the various concepts of health and illness and also explain the postmodern perspectives of health and illness in different ways.